New system makes argon recovery in the production of solar ingots possible. Issue 4 (October 2015) - Grant, Rob
Abstract : Dr. Rob Grant explains how new chemical looping combustive purification technology, developed in conjunction with Cambridge University, has made point of use argon recovery possible. For solar PV silicon ingot producers the technology could see the cost of this element of production reduced by 95%, he suggests.